Easter Island, earth island the enigmas of Rapa Nui - Bahn, Paul G. 1953-; Flenley, John (Rowman & Littlefield, 2017)
"Easter Island, isolated deep in the South Pacific and now a world heritage site, was home to a fascinating prehistoric culture--one that produced massive stone effigies (the moai) and the birdman cult--yet much of the island's past remains shrouded in mystery. Where did the islanders come from, and when? How did Rapa Nui culture evolve over the centuries? How, and why, did their natural environment change over time? Paul Bahn and John Flenley guide readers through the enigmas of Rapa Nui, incorporating the records of early explorers, folk legends, and archaeological evidence along the way. They cover the island's geological and environmental history and explore its flora and fauna, illustrating how human actions affected the natural environment of the island. This fourth edition draws on recent DNA studies of ancient human and animal bones as well as plant remains and the evolving understandings of how the moai were transported."--Back cover
Keywords: Geschichte; Europäer; Entdeckung; Indigenes Volk; Siedlung; Kultur; Osterinsel; Prehistoric peoples / Easter Island; Sculpture, Prehistoric / Easter Island; Easter Island / History; Easter Island / Antiquities; Antiquities; Prehistoric peoples; Sculpture, Prehistoric; Easter Island; History